PERAN DAN IMPELEMENTASI STRATEGI PENGEMBANGAN DISBUDPAR KAB. SUMBA TENGAH PROVINSI NTT DALAM PEMBANGUNAN PARIWISATA (SUATU PENDEKATAN KUALITATIF) - Roku, Yelince Rambu; Mahagangga, I Gst. Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i02.p14, 2016)
Facts indicate the potential of tourism in the Central Sumba Regency has not been able to attract tourist arrivals. The role stakeholders, especially SKPD Department of Culture and tourism (Disbudpar) Central Sumba Regency have a heavy duty to make tourism development. The method used was a case study approach (inductive) using qualitative methods. Data were analyzed using qualitative data analysis techniques with presentation techniques qualitative descriptive data. The results of this research are the role Disbudpar Kab. Central Sumba in tourism development constrained human resources issues and other findings are necessary translation of roles more effectively and efficiently with attention to personal ability, social skills and intellectual abilities in the future culture. The next finding is the difficulty Disbudpar Kab. Central Sumba in the implementation of the work plan caused by many factor. It is important to consider in the future development of tourism is the attention to the internal and external coordination and the determination of the potential market rating that will facilitate the development of tourism attractions such as the establishment or featured travel products and preparation of human resources, infrastructure and other supporting facilities.
Keywords: Strategy, Implementation, Strategy, Development, Tourism